Heatwaves hinder mussel invasion by weakening byssus production - Xin Xu; Ke Yang; Yong Liu; Yuewen Deng; Liqiang Zhao; Liqiang Zhao (Frontiers in Marine Science, 2023)
Heatwaves and bioinvasion are among the most pressing ecological issues worldwide. The highly invasive South American mussels (Mytella strigata) can construct extremely dense byssal mats in intertidal habitats they invade, causing serious threats to local biodiversity and ecosystems. Yet, little is known about whether intensifying heatwaves might facilitate their invasions. Here, we investigated how the byssus production of M. strigata responds to heatwaves scenarios that have frequently occurred in recent years in the South China Sea. Compared with those grown at ambient temperature, mussels exposed to simulation heatwaves secreted significantly lowered number, length, and diameter of byssal threads, and exhibited significant impairments in the adhesion of byssus. Differential expressions of key genes involved in byssus production (e.g., foot protein gene, cell apoptosis gene, extracellular matrix-receptor interaction gene, and neuroactive ligand-receptor interaction gene) offered deeper insights into heatwaves-induced physiological changes in byssal gland. These results can provide an improved understanding of responses of mussel byssus production to intensifying heatwaves and take a major leap forward in examining the dispersal of highly invasive species in a rapidly warming ocean.